Physical performance of elite New Zealand Olympic class sailors - Legg, S. J.; Miller, A. B.; Slyfield, D.; Smith, P.; Gilberd, C.; Wilcox, H.; Tate, C. (The Journal of Sports Medicine and Physical Fitness, 1997)
OBJECTIVE: The purpose of this study was to compare the physical performance of elite New Zealand and other nations olympic class sailors and to undertake an initial examination of the relation between physical and sailing performance. EXPERIMENTAL DESIGN: A comparative study. SETTING: Healthy elite national level olympic class sailors were examined. PARTICIPANTS: Thirty-one elite New Zealand Olympic sailing squad team members and 108 Olympic team sailors from ten other nations. INTERVENTIONS: The data for the two groups of subjects was compared using unpaired "t"-tests. A qualitative analysis was used to examine the relation between physical and sailing performance. MEASURES: Measurements included age, body mass, muscular strength endurance (as assessed by the maximum number of push-ups, pull-ups and sit-ups that could be performed) and serobic power (as assessed by the time taken to cover 2500 m and the distance completed in 12 minutes in a maximal effort rowing ergometer test). Sailing performance was assessed by national coach ranking of each New Zealand sailor. RESULTS: On average the New Zealanders were younger and lighter than the sailors from the other nations. They tended to have greater shoulder/arm strength endurance as reflected in their performance for push-ups and pull-ups, but a lesser ability in their sit-up performance. They also tended to be aerobically fitter. There were clear and logical differences between body mass and both class of vessel and the position of the sailor i.c. crew or helmsman. Lighter sailors sailed lighter craft whilst heavier sailors sailed the heavier craft. Crew members were generally heavier than helmsmen. Age appeared to be related to sailing performance. CONCLUSIONS: Elite New Zealand Olympic class sailors tend to be younger, lighter, stronger and aerobically fitter than elite sailors from other nations. Age appeared to be related to on-water sailing performance.